Maintenance Inhalers for Asthma and COPD in Spain. - Muñoz, Xavier; Giner, Jordi; Sicras, Antoni; Lo Re, Daniele (Respiratory Care, 2024)
BACKGROUND: This study aimed to describe the use of pressurized metered-dose inhalers (pMDIs) and dry powder inhalers (DPIs) in Spanish subjects in terms of sociodemographic, clinical, and functional characteristics in subjects with asthma or COPD on maintenance treatment with inhaled therapy. METHODS: This was a retrospective, descriptive, national, multi-center, and observational study using a database with 1.8 million patients from hospitals and primary care centers as a secondary information source. RESULTS: The sample included 24,102 subjects with asthma on maintenance therapy (26.0% with pMDI, 55% with DPI, and 19.0% with a combination of DPI + pMDI inhalers) and 12,858 subjects with COPD on maintenance therapy (26% with pMDI; 39% with DPI; and 35% with a combination of pMDI + DPI inhalers, mostly extemporary triple therapy). In proportion, subjects ≥ 75 y old used more pMDI than DPI, while younger subjects (40-64 y old) used more DPI. An inhalation chamber was prescribed in 51.0% of subjects with asthma and 47.2% of subjects with COPD treated with pMDI. The use of an inhalation chamber increases with the degree of air-flow limitation by disease and age. In subjects with comorbidities, pMDI inhaler use increased in those ≥ 75 y old for subjects with asthma and subjects with COPD. Switching from pMDI to DPI and vice versa was relatively common: 25% of subjects with asthma and 21.6% of subjects with COPD treated with pMDI had switched from DPI in the previous year. On the contrary, 14.1% and 11.4% of subjects with asthma and subjects with COPD, respectively, treated with DPI had switched from pMDI the last year. CONCLUSIONS: The use of pMDI or DPI can vary according to age, both in asthma and COPD. Switching from pMDI to DPI and vice versa is relatively common. Despite the availability of dual- and triple-therapy inhalers on the market, a considerable number of subjects were treated with multiple devices.